Preparation method of PyC-SiC-HfC triple interface phase modified C / C-SiBCN double matrix anti-ablation composite material

Through the PyC-SiC-HfC three-interface phase modification method, C/PyC-SiBCN composite material was prepared, which solved the problem of insufficient ablation performance caused by weak interface phase of the C/C composite material, and achieved excellent ablation resistance with high density and low porosity.

CN115417699BActive Publication Date: 2025-04-29SHANGHAI UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211067510.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-04-29
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The ablation resistance of existing C/C composite materials is insufficient, especially the weakness of the interface phase, which leads to an overall retreat of the ablation surface. The existing modification methods have failed to effectively improve the ablation resistance of the interface phase.

Method used

The PyC-SiC-HfC three-interface phase modification method was used to prepare PyC and SiC interface phases on the surface of the carbon fiber prefabricated body through the CVD and CVI processes, and the SiBCN matrix was prepared in combination with the PIP process to form a C/PyC-SiC-HfC/C-SiBCN composite material.

Benefits of technology

The ablation resistance of the composite material was significantly improved, with a density of 1.7-1.9 g/cm3, a porosity of 4-5vol%, and the ablation rate of oxyacetylene flame ablation experimental line was reduced to 2μm/s.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115417699B_ABST
    Figure CN115417699B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a PyC-SiC-HfC triple interface phase modified C / C-SiBCN double matrix anti-ablation composite material, comprising the preparation of a PyC-SiC-HfC interface phase and a C-SiBCN matrix, and specifically comprising: (1) preparing a PyC+SiC interface phase on a fiber surface of a carbon fiber preform by a CVD process to obtain a preform with an interface phase of a certain thickness; (2) dipping the preform obtained in step (1) in a HfC polymer-xylene solution for multiple times to obtain a PyC-SiC-HfC triple interface phase modified carbon fiber preform material; (3) preparing a C matrix by a CVI process; (4) preparing a SiBCN modified matrix by a PIP process; (5) curing and cracking; (6) repeating steps (4) and (5) to finally obtain a C / PyC-SiC-HfC / C-SiBCN composite material. The present invention adopts a three-interface complementary high-temperature resistant system of PyC-SiC-HfC, and utilizes the good lamellar structure of PyC, the good anti-ablation performance of HfC and the good thermal expansion coefficient matching ability of SiC as the interface phase of the C / C-SiBCN composite material, so as to improve the anti-ablation performance of the entire composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a PyC-SiC-HfC triple interface phase modified C / C-SiBCN double matrix anti-ablation composite material. Background Art

[0002] Hypersonic aircraft are the main development direction of aerospace. Since the aircraft has to move at high speed for a long time in the atmosphere, the high Mach aerodynamic heating and high-temperature airflow heating generated put forward very high requirements on the structural materials of the aircraft. The protective materials are required to have not only the good properties of light weight and high strength, but also excellent anti-ablation performance.

[0003] C fiber reinforced C matrix composite material is commonly known as C / C composite material, which is a composite material with many advantages such as low density, high specific strength, high modulus, high thermal conductivity, high specific heat capacity, and relatively good thermal shock resistance and wear resistance, etc., obtained by chemical vapor infiltration (CVI) process with carbon fiber or carbon fiber fabric such as carbon cloth, carbon felt, etc. as reinforcement and C as matrix. Due to the low oxidation temperature of carbon materials, the commonly used methods for improving the ablation resistance of C / C composite materials are mainly to improve the carbon fiber preform and pyrolytic carbon texturing technology, matrix modification technology and external anti-ablation coating count, and there is little research on the method of multi-interface phase modification combined with matrix phase modification.

[0004] According to the protection mechanism of anti-ablation composite materials, two composite material protection systems are divided: coating material system and fiber / matrix modification system. As for the coating material system, the coating material itself should have high melting point, high mechanical properties, good adhesion, suitable expansion coefficient and other characteristics. According to the above characteristics, the commonly used coating materials can be divided into the following categories according to their main components: silicon-based ceramic coating, boron-based ceramic coating, metal oxide coating, metal carbide coating, etc.

[0005] The fiber / matrix modification system of C / C composites can be further divided into matrix phase modification and interface phase modification: Matrix modification is achieved by introducing one or more of SiC, HfC, ZrC, ZrB2, MoSi2 or other metal ions into the matrix, which can be divided into single-phase, two-phase, multi-phase and metal element modified C / C composites. The advantage of the matrix modification system of C / C composites over the interface phase is that it reduces the requirement for strong bonding between the interface phase and the matrix material. Although the doped material and the matrix material are still required to have similar thermal expansion coefficients, the more dispersed the dopants are, the lower the stringent requirements for the expansion coefficient.

[0006] The interface phase modification process is an anti-ablation material modification process proposed based on the starting point of fiber protection. Usually, the anti-ablation performance of composite materials is jointly affected by the matrix, fiber and the interface between the two. The interface often has a larger specific surface area and higher interface energy, so the interface often becomes a weak phase in C / C composite materials. When the fiber is ablated into a needle-like shape, the entire ablation surface often forms an overall receding form. Generally speaking, the graphitized carbon layer structure is more suitable as the interface phase of C / C composite materials. It provides a weak chemical bond between carbon fiber and carbon matrix, which is necessary to promote toughening. In order to achieve the protection of carbon fiber, a certain thickness of BN or SiC interface is often prepared at the fiber interface, and the oxidation products of these two interfaces are used to protect the fiber, thereby further enhancing the anti-ablation performance of the composite material. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a PyC-SiC-HfC triple interface phase modified C / C-SiBCN double matrix anti-ablation composite material, which has solved the problems existing in the prior art.

[0008] The present invention can be solved by the following technical solutions:

[0009] A method for preparing a PyC-SiC-HfC triple interface phase modified C / C-SiBCN dual matrix anti-ablation composite material comprises the preparation of a PyC-SiC-HfC interface phase and a C-SiBCN matrix, and specifically comprises: (1) preparing a PyC+SiC interface phase on a fiber surface of a carbon fiber preform by a CVD process to obtain a preform with an interface phase of a certain thickness; (2) immersing the preform obtained in step (1) in a HfC polymer-xylene solution for multiple times to obtain a PyC-SiC-HfC triple interface phase modified carbon fiber preform material; (3) preparing a C matrix by a CVI process; (4) preparing a SiBCN modified matrix by a PIP process; (5) curing and cracking; (6) repeating steps (4) and (5) to finally obtain a C / PyC-SiC-HfC / C-SiBCN composite material.

[0010] Furthermore, the carbon fiber preform is a 2D laminated carbon fiber.

[0011] Furthermore, the carbon source selected for depositing the PyC interface is C3H6 or CH4 alkane gas, the deposition pressure is 10-20KPa, the deposition time is 10-15h, the deposition temperature is 950-1000°C, and the deposition residence time is 0.5-1s.

[0012] Furthermore, the gas source selected for depositing the SiC interface is MTS+H2+N2, the deposition pressure is 10-20KPa, the temperature is 1050°C, and the deposition time is 12-15h.

[0013] Furthermore, in the step 2), the immersion time in the HfC polymer-xylene solution is 2-5 hours, the immersion mass fraction is 13-15, and the heat treatment temperature used is 1500-1600°C according to the temperature of generating hafnium carbide crystals.

[0014] Furthermore, in step 3), the designed carbon matrix density is 1.2-1.4 g / cm 3 The selected gas source is CH4 or C3H6 alkane gas, the deposition pressure is 100-200mbar, the gas residence time is 0.5-1s, and the deposition time is 10-14h.

[0015] Furthermore, in the step 4), the polyborosilazane precursor has a boron content of 1-2%, a viscosity of 1000-3000 cp, a molecular weight of 600-900, and a ceramic curing yield of >60%.

[0016] Furthermore, in the step 4), N2 is used as the atmosphere for pressurization, the pressure of the pressurized impregnation is 1-2 MPa, and the impregnation time is 4-6 hours.

[0017] Furthermore, in the step 5), the PBSZ polymer precursor is cross-linked and cured, the cross-linking and curing temperature is 170-300° C., and the curing time is 2-4 hours; the pyrolysis temperature is 1000-1200° C., and the time is 2-4 hours.

[0018] Furthermore, the density of the C / PyC-SiC-HfC / C-SiBCN composite material is 1.7-1.9 g / cm 3 , the porosity is 4-5vol%.

[0019] Beneficial Effects

[0020] The present invention adopts a three-interface complementary high-temperature resistant system of PyC-SiC-HfC, and utilizes the good lamellar structure of PyC, the good anti-ablation performance of HfC and the good thermal expansion coefficient matching ability of SiC as the interface phase of the C / C-SiBCN composite material, so as to improve the anti-ablation performance of the entire composite material. The density of the prepared C / PyC-SiC-HfC / C-SiBCN composite material reaches 1.7-1.9g / cm 3 , the porosity is 4-5vol%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1Schematic diagram of the process of the present invention

[0022] Figure 2 Schematic diagram of the microstructure of the ablation center area in the present invention DETAILED DESCRIPTION

[0023] The following describes the implementation of the present invention through specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0024] Embodiment 1:

[0025] A PyC-SiC-HfC triple interface phase modified C / C-SiBCN dual matrix anti-ablation composite material, reference Figure 1 As shown, the preparation method is as follows:

[0026] Preparation of pyrolytic carbon interface phase and silicon carbide interface phase: The cut 2D carbon felt stack is placed in a graphite mold, and then the mold is placed in a chemical reaction deposition furnace. The specific parameters are set as follows: pressure: 100mbar; gas residence time in the mold: 0.5s; temperature: 965℃. The gas flow rate is calculated according to the relationship between residence time, deposition temperature and pressure by the following formula:

[0027]

[0028] When pyrolytic carbon is deposited for 90 min under this parameter, a PyC interface layer with a thickness of about 250 nm can be prepared on the sample surface.

[0029] The preform of the prepared PyC interface layer is placed in a mold, and the mold is placed in the deposition position in a gas deposition furnace. A gas source with a gas composition of MTS-H2-N2 is used as a reaction precursor system. The detailed interface preparation parameters are as follows: gas ratio: MTS (methyltrichlorosilane): H2: N2 = 1:5:4; temperature: 1050°C; pressure: 100 mbar, gas residence time in the mold: 0.5 s; then the remaining volume of the relevant mold is calculated and measured, and the total gas flow rate is calculated using formula (1), and then the relevant gas flow rate is calculated according to the proportional relationship.

[0030] Preparation of hafnium carbide interface phase: Measure the volume and mass of the preform, measure the density of the composite material according to the Archimedes drainage method, and select the hafnium carbide interface with a design mass fraction of 13%. Using the impregnation cracking process, place the carbon fiber preform with the double interface deposited above in the hafnium carbide impregnation liquid for 2 hours, place the carbon fiber preform impregnated with the hafnium carbide impregnation liquid in a tubular furnace and heat it to 1500°C, so that the impregnation liquid is converted into hafnium carbide crystals, and calculate the mass change. Then, the above process is repeated multiple times to make the impregnation mass fraction reach 13%.

[0031] Preparation of carbon matrix by CVI process: According to preliminary calculations, when the density of the C matrix reaches 1.3% or less, the SiBCN matrix will maintain its continuity. In order to make the SiBCN matrix continuous, the designed carbon matrix density is 1.25g / cm 3 The carbon source and preparation method of the C matrix are similar to those of the PyC interface. C3H6 is used as the carbon source for the reaction. The deposition pressure is 100 mbar, the gas residence time is 0.5 s, and the deposition time is set to 12 h to prepare a denser composite material. At this time, the density of the deposited preform is about 1.3 g / cm 3 , to achieve a predetermined preform density.

[0032] Preparation of SiBCN matrix by PIP: The composite material with the C matrix deposited above is cut into a predetermined shape and placed in a pressure reactor. An external vacuum pump is connected to drain the air in the reactor. PBSZ is added to the reactor until the sample is completely impregnated. In order to improve the impregnation efficiency, N2 is used as the atmosphere for pressurization. The applied pressure is 1MPa and the impregnation time is 4h to obtain a C / SiBCN composite embryo. Secondly, the cross-linking and curing of the PBSZ polymer precursor is carried out: the temperature in the reactor is raised to 170°C (the pressure of the entire system is still maintained at 1MPa) by using the heating device of the pressure reactor itself. The curing time is 2h, the heating device is turned off, and the sample is cooled to room temperature with the reactor. Finally, the ceramic transformation process is carried out: the sample is taken out of the reactor and transferred to a high-temperature tubular furnace to complete ceramicization at 1000°C for pyrolysis ceramicization. The protective atmosphere is N2 and the time is 2h. This process is repeated 5 times to obtain a relatively dense composite material (density 1.87g / cm 3 , porosity 4.75 vol%).

[0033] Oxyacetylene ablation experiment: Oxyacetylene flame ablated the composite material for 60 seconds, and the measured linear ablation rate was only 2μm / s. The microstructure of the ablation center area is as follows: Figure 2 shown.

[0034] Comparative Example 1:

[0035] The preparation process is similar to the above, except that the hafnium carbide interface phase is not prepared, that is, the prepared material is a PyC-SiC double interface phase modified C / C-SiBCN double matrix anti-ablation. The density of the composite material finally prepared in this experiment is 1.81g / cm 3 , porosity: 5.42 vol%.

[0036] After 60s of oxyacetylene flame ablation, the linear ablation rate was 31μm / s.

[0037] Comparative Example 2:

[0038] The preparation process is similar to the above, except that the SiBCN matrix phase is not prepared, and the C matrix phase is used, that is, the prepared material is a PyC-SiC-HfC three-interface phase modified C / C composite material. The density of the composite material finally prepared in this experiment is 1.72g / cm 3 , porosity: 6.21 vol%.

[0039] After 60s of oxyacetylene flame ablation, the linear ablation rate was 19μm / s.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PyC-SiC-HfC triple interface phase modified C / C-SiBCN dual matrix anti-ablation composite material, characterized in that: The preparation method is as follows: Preparation of pyrolytic carbon interface phase and silicon carbide interface phase: The cut 2D carbon felt stack is placed in a graphite mold, and then the mold is placed in a chemical reaction deposition furnace. The specific parameters are set as follows: pressure: 100 mbar; gas residence time in the mold: 0.5 s; temperature: 965 ° C. The gas flow rate is calculated by the following formula based on the relationship between residence time, deposition temperature and pressure: (1) When pyrolytic carbon was deposited for 90 min under this parameter, a PyC interface layer with a thickness of 250 nm was prepared on the sample surface; The preform of the prepared PyC interface layer is placed in a mold, and the mold is placed in the deposition position of a gas deposition furnace. A gas source with a gas composition of MTS-H2-N2 is used as a reaction precursor system. The detailed interface preparation parameters are as follows: gas ratio: MTS: H2: N2 = 1:5:4; temperature: 1050°C; pressure: 100mbar, gas residence time in the mold: 0.5s; then the relevant mold free volume is calculated and measured, and the total gas flow rate is calculated using formula (1), and then the relevant gas flow rate is calculated according to the proportional relationship; Preparation of hafnium carbide interface phase: Measure the volume and mass of the preform, measure the density of the composite material according to the Archimedes drainage method, select the hafnium carbide interface with a design mass fraction of 13%, use the impregnation cracking process, place the carbon fiber preform with the double interface deposited above in the hafnium carbide impregnation liquid for 2 hours, place the carbon fiber preform impregnated with the hafnium carbide impregnation liquid in a tubular furnace and heat it to 1500°C to convert the impregnation liquid into hafnium carbide crystals, calculate the mass change, and then repeat the above process multiple times to make the impregnation mass fraction reach 13%; CVI process for preparing carbon matrix: After preliminary calculation, the carbon fiber preform is first subjected to a certain amount of carbon matrix deposition to obtain a low-density C / C preform with a density value of ≤1.3g / cm 3 When the SiBCN matrix is ​​heated to 12 ℃, the SiBCN matrix will maintain its continuity. The carbon source and preparation method of the carbon matrix are similar to those of the PyC interface. C3H6 is used as the carbon source for the reaction. The deposition pressure is 100 mbar, the gas residence time is 0.5 s, and the deposition time is set to 12 h to prepare a denser composite material. At this time, the density of the deposited C / C preform is 1.3 g / cm 3 , reaching a predetermined preform density; Preparation of SiBCN matrix by PIP: the composite material with the carbon matrix deposited above was cut into a predetermined shape and placed in a pressure reactor. The air in the reactor was evacuated by an external vacuum pump. PBSZ was added into the reactor until the sample was completely impregnated. In order to improve the impregnation efficiency, N2 was used as the atmosphere for pressurization. The applied pressure was 1MPa and the impregnation time was 4h to obtain a C / SiBCN composite material embryo. Secondly, the cross-linking and curing of the PBSZ polymer precursor was carried out: the temperature in the reactor was raised to 170°C by the heating device of the pressure reactor itself, and the pressure of the entire system was still maintained at 1MPa. The curing time was 2h, the heating device was turned off, and the sample was cooled to room temperature with the reactor. Finally, the ceramic transformation process was carried out: the sample was taken out of the reactor and transferred to a high-temperature tubular furnace to complete ceramicization at 1000°C for pyrolysis ceramicization. The protective atmosphere was N2 for 2h. The process was repeated 5 times to obtain a relatively dense composite material. The density of the composite material was 1.87g / cm 3 , porosity 4.75vol%, Oxyacetylene ablation experiment: The composite material was ablated by oxyacetylene flame for 60 seconds, and the measured linear ablation rate was only 2μm / s.

Citation Information

Patent Citations

  • Carbon fiber-reinforced (carbon-) silicon carbide base-ultra-high temperature ceramic base compound material and production method thereof

    CN109970460A

  • Modified C / SiC composite material and preparation method thereof

    CN112299865A